Program Acara Kesenian Tradisional Di Radio Swasta Lokal Di Diy (Studi Komparatif Tentang Faktor-Faktor Yang Mempengaruhi Eksistensi Program Acara Kesenian Tradisional Di Radio Siaran Swasta Pada Frekuensi FM Dan AM Di Yogyakarta) - Noning Verawati (KOM & REALITAS SOSIAL, 2012)
This research is a case study research that revealing how is the existence of traditional art program (Wayangan) on four private broadcast radios at Jogjakarta with different frequency that consist of Frequency Modulation (FM) and Amplitude Modulation (AM) in Unisi Radio 104.5 FM, Retjo Buntung Radio 99.4 FM, Swara Konco Tani Radio and Swara Kenanga Jogjakarta Radio. Appropriate with case study, so this research will answering the question âhowâ and âwhyâ about the factors that influenced to the traditional art program on the private broadcast radio at Jogjakarta. The traditional art program, especially wayang was being a research object because this program has a high historic value in order to maintaining the origin culture of Indonesia. Initially, this program is âcreationâ government program as one of broadcast requirement. But after the reformation on 1998, this program is no longer being a requirement so that there are many the private broadcast radios in FM frequency is not broadcasting it, but there are also still broadcasting it although in limited duration. Today, the traditional art program can listened on the private broadcast radio in AM frequency that has taking over these programs. This research result is Unisi Radio 104.5 FM has been removing the art program because it is not agree with their audients and segment that is young generation. While Retjo Buntung Ra dio on the contrary is choosing to maintain the traditional art program because they were committed to maintaining Indonesian culture. Meanwhile, two radio that placed in AM that consist of Swara Konco Tani and Swara Kenanga instead carrying the traditional art program as their main broadcast, so that they are famous as radio that based on culture.